Adoption of Universal Testing in Endometrial Cancers for Microsatellite Instability Using Next-Generation Sequencing - Rodriguez, Isabel V; Strickland, Sarah; Wells, David; Manhardt, Enna; Konnick, Eric Q; Garcia, Rochelle; Swisher, Elizabeth; Kilgore, Mark; Norquist, Barbara (JCO precision oncology, 2023)
To assess implementation of a next-generation sequencing (NGS) assay to detect microsatellite instability (MSI) as a screen for Lynch syndrome (LS) in endometrial cancer (EC), while determining and comparing characteristics of the four molecular subtypes. A retrospective review was performed of 408 total patients with newly diagnosed EC: 140 patients who underwent universal screening with NGS and 268 patients who underwent screening via mismatch repair immunohistochemistry (MMR IHC) as part of a historical screening paradigm. In the NGS cohort, incidental and mutations along with MSI were identified and used to characterize EC into molecular subtypes: -ultramutated, MSI high (MSI-H), -mutated, and no specific molecular profile (NSMP). In historical cohorts, age- and/or family history-directed screening was performed with MMR IHC. Statistical analysis was performed using a -test for continuous variables and chi-square or Fisher's exact test for categorical variables. In the NGS cohort, 38 subjects (27%) had MSI-H EC, 100 (71%) had microsatellite stable EC, and two (1%) had an indeterminate result. LS was diagnosed in two subjects (1%), and all but five patients completed genetic screening (96%). Molecular subtypes were ascertained: eight had -ultramutated EC, 28 had -mutated EC (20%), and 66 (47%) had NSMP. MSI-H and -mutated EC had worse prognostic features compared with NSMP EC. Comparison with historical cohorts demonstrated a significant increase in follow-up testing after an initial positive genetic screen in the MSI NGS cohort (56% 89%; = .001). MSI by NGS allowed for simultaneous screening for LS and categorization of EC into molecular subtypes with prognostic and therapeutic implications.